2013
DOI: 10.1007/s00167-013-2400-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined ACL reconstruction and closing-wedge HTO for varus angulated ACL-deficient knees

Abstract: The described technique allowed patients with medial OA, varus alignment and chronic ACL deficiency to restore knee laxity, correct alignment and resume a recreational level of activity at 6.5 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 25 publications
4
100
2
1
Order By: Relevance
“…16 Numerous studies have investigated combined approaches of osteotomy and ACLR in early or imminent osteoarthritis as salvage procedures for young patients. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] Only 1 of these studies (including 4 patients) has used the latest generation of implants (angular stable plate fixator). 20 So far, no study has investigated cases of severe osteoarthritis or combined chondral resurfacing (CR) or cartilage restoration procedures.…”
mentioning
confidence: 99%
“…16 Numerous studies have investigated combined approaches of osteotomy and ACLR in early or imminent osteoarthritis as salvage procedures for young patients. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] Only 1 of these studies (including 4 patients) has used the latest generation of implants (angular stable plate fixator). 20 So far, no study has investigated cases of severe osteoarthritis or combined chondral resurfacing (CR) or cartilage restoration procedures.…”
mentioning
confidence: 99%
“…17 and finally to protect a concurrent ligament reconstruction. 18 It has been reported that performing a PTO to treat symptomatic medial compartment osteoarthritis in selected patients has a survival rate of 94% at 3.6 years postoperatively. 11 The mean preoperative modified Cincinnati Knee Score improved from 42.9 (range, 8 to 63) to 65.1 (range, 10 to 100); significant differences were also observed in International Knee Documentation Committee scores both for effusions and for the single-leg hop.…”
Section: Discussionmentioning
confidence: 99%
“…Indications have recently expanded to the treatment of several entities such as medial compartment overload or early degenerative changes, 12 chronic instability (such as posterolateral corner, 13 PCL, and anterior cruciate ligament instability), 5 and ligament reconstruction failure due to malalignment, 12 as well as the protection of a concurrent ligament reconstruction. 3 Likewise, this anterolateral high tibial osteotomy may be useful when both sagittal tibial slope and valgus coronal alignment corrections are required to protect a PCL or medial knee ligament reconstruction, as well as in cartilage procedures.…”
Section: Discussionmentioning
confidence: 99%
“…P roximal tibial osteotomy (PTO) has been reported to successfully treat medial knee overload, early unicompartmental osteoarthritis, and chronic instabilities. [1][2][3][4][5] This procedure has been primarily advocated for treatment of varus misalignment, leaving the distal femur as the preferred site for correction of valgus deformity. 6 When treating biplanar abnormalities (coronal and sagittal planes), distal femoral osteotomies fail to address the sagittal plane, specifically the tibial slope.…”
mentioning
confidence: 99%